Peningkatan Daya Saing Kopi Arabika origin Timor Tengah Selatan - Setiawan, Krisna; Tiri, John Tibo Kana (JURNAL AGRICA, 2024)
Arabica coffee in South Central Timor Regency (TTS) has an important role as a superior commodity that has the opportunity to compete in the global market. However, currently the main focus is on how to improve competitiveness strategies in addition to coffee added value so that TTS origin arabica coffee has comparative and competitive advantages. This study aims to analyze the comparative and competitive competitiveness of TTS origin arabica coffee and formulate appropriate strategies to improve the competitiveness of the coffee. Determination of the number of respondents using quota sampling technique as many as 30 respondents and data analysis methods using Policy Analysis Matrix (PAM) and SWOT matrix. The results showed that TTS origin arabica coffee has a very high competitiveness and is highly prioritized to be developed by the government and local communities based on the results of the analysis of private benefits and social benefits as well as the analysis of competitive advantages and comparative advantages, all of which (PP, SP, PCR, DRC) provide positive values according to the competitiveness assessment criteria. From the results of the SWOT matrix analysis, growth oriented strategy (quadrant I) is the chosen strategy  where the S-O strategy is the right choice to improve the competitiveness of TTS origin arabica coffee, namely: increasing production by utilizing the availability of land and human resources, maintaining the quality and uniqueness of coffee flavors, and establishing partnerships with the government and coffee suppliers